1998
DOI: 10.1143/jjap.37.l1087
|View full text |Cite
|
Sign up to set email alerts
|

Selective Area Growth of Si on Thin Insulating Layers for Nanostructure Fabrication

Abstract: A new method of fabricating Si microstructures on thin insulating films is described. It combines selective-area growth of Si with electron-beam direct patterning of a SiO 2 /SiN x bilayer mask. The chemical composition of the top SiO 2 layer of the mask can be modified locally by electron-beam irradiation. The different chemical properties between irradiated and nonirradiated surfaces make it possible to deposit Si only on the irradiated surface. The bottom SiN x layer is stable against electron-beam irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Because the amount of SiO 2 on the surface of alkylated samples was very small, it was not possible to collect spectra of the SiO 2 signal (72-76 eV) in a short enough amount of time to prevent beam damage. Instead, signals from the Si LVV (90-92 eV) [18][19][20] and O KLL (510 eV) 21 regions were combined to determine areas of SiO 2 in the SAM image. Spectra were collected with the electron analyzer held in the Si LVV region (92 eV) and the O KLL region (510 eV), which were then superimposed to create a composite image of Si and SiO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Because the amount of SiO 2 on the surface of alkylated samples was very small, it was not possible to collect spectra of the SiO 2 signal (72-76 eV) in a short enough amount of time to prevent beam damage. Instead, signals from the Si LVV (90-92 eV) [18][19][20] and O KLL (510 eV) 21 regions were combined to determine areas of SiO 2 in the SAM image. Spectra were collected with the electron analyzer held in the Si LVV region (92 eV) and the O KLL region (510 eV), which were then superimposed to create a composite image of Si and SiO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For plasma oxidation of the SiN x layer described in §3. 3,9,10) the the substrate surface is likely to play an important role. Related to this issue, we previously compared Si deposition processes on SiO 2 and SiN x surfaces for the purpose of selective-area growth.…”
Section: Methodsmentioning
confidence: 99%
“…Related to this issue, we previously compared Si deposition processes on SiO 2 and SiN x surfaces for the purpose of selective-area growth. 9,10) We found that the initial growth processes on these two surfaces are distinctly different when Si growth is carried out in a thermal chemical vapor deposition (CVD) mode. In particular, it was observed that the shape of the Si nuclei on SiO 2 is ball-like while those on SiN x wet on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier experimental investigations [1][2][3] have demonstrated that upon electron irradiation a silica surface undergoes changes in not only photosensitivity but also surface reactivity, mainly due to irradiation-induced defects. Oxygen deficient centers (ODCs) are the most common point defects in oxide materials [4 -6].…”
mentioning
confidence: 99%